Mechanical properties and microstructure of hybrid alkali-activated cement component - Dener, Murat; Karatas, Mehmet; Shi, Jinyan; Mohabbi, Mehrzad (Springernature, 2024)
Portland cement (PC), which has been used as a dominant binder material in concrete since its development, is responsible for approximately 8% of global anthropological CO2 emissions. Alkali-activated materials, which are based on the activation of precursor materials using alkali activators, are binders developed for environmental gains. The significance of this study lies in exploring the mechanical and microstructure properties of hybrid alkali-activated cements containing PC, produced under various parameters. This investigation provides valuable insights into optimizing the composition and processing conditions for these materials. In this study, 34 mixtures were produced to investigate the Na2SiO3 to NaOH ratio (2, 2.5, and 3), PC substitution level (5%, 10%, 15%, 20%, and 25%) and curing temperature (25, 50, 75 and 100 degrees C) effects on the hybrid alkali-activated slag/PC components. The highest compressive strength was obtained at 15% PC substitution. As the Na2SiO3 to NaOH ratio increased, the compressive strength of the samples containing 0, 5%, 10% and 15% PC increased. However, the increase in the Na2SiO3 to NaOH ratio negatively affected the compressive strength of the samples containing more than 15% PC. The highest compressive strength in both partially PC-substituted and fully slag samples was achieved when the samples were cured at 50 degrees C. When the sample containing 100% slag was cured at 50 degrees C, the degree of hydration was higher compared to the sample cured at 25 degrees C. In the sample with 15% PC, a sharp band corresponding to the Si-O bond was observed at 25 degrees C. However, as the curing temperature exceeded 50 degrees C, this band became broader and weaker. This indicates that the amount of hydration products in the PC-blended alkali-activated slag sample decreased at curing temperatures above 50 degrees C.
Keywords: Alkali-activated cement; Blast furnace slag; Portland cement; Compressive strength; Microstructure